KEMISKINAN PENDUDUK DAERAH ALIRAN IRIGASI DAN DAERAH ALIRAN SUNGAI (DAS) DI KABUPATEN MUSI RAWAS - Andry Andry; Edy Humaidi (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2018)
The objectives of this research are to know the characteristics of poor people in irrigation and watershed areas, to analyze the difference of income of the poor in irrigation and watershed areas, to analyze income inequality of the poor in irrigation and watershed areas. The study used primary and secondary data types. Primary data collection techniques obtained through Interview / Questionnaire with respondents. The analytical technique used is descriptive analysis to obtain the characteristics of the respondents, and the analysis of different test to obtain the income ratio of respondents, then gini ratio analysis to obtain the gini coefficient or income inequality of respondents. The results of this study are: Poor people in irrigation areas tend to have a narrower area of land than watersheds, 69 Percent of irrigated dwellers are at productive age (15-54) whereas river basin is 91 percent, the majority of the poor irrigation flows are rice farms and rubber streams. The income of the poor in the irrigation flow areas is significantly different from the income of the poor in the watershed, as seen from the different test results t hit> t table (6,009> 1.67), with the average income of the poor in the irrigation flow area of Rp. 1.858.377 per month while the poor in the watershed area Rp. 1,173,014 per month. The inequality of income of poor population of irrigation flow area is 0,09 whereas poor population of river basin is 0,27.